Redefining procurement paradigms: A critical review of buyer-supplier dynamics in the global petroleum and natural gas industry - Alhammadi, Ali; Soar, Jeffrey; Yusaf, Talal F.; Ali, Bashar Mahmood; Kadirgama, Kumaran (Elsevier Ltd, 2023)
This paper reviews critique of procurement approaches within the petroleum and natural gas sectors, whilst concurrently unveiling and scrutinizing the elements that amplify and shape the buyer-supplier interactions within this industry. The primary objective of this review is to redefine procurement paradigms in the global petroleum and natural gas industry by reassessing the dynamics between buyers and suppliers. The findings from our study reveal a noticeable gap in the literature concerning the fortification of buyer-supplier relationships in the petroleum and natural gas sector. While existing studies offer valuable insights into procurement trends, they significantly lack focus on strengthening these key relationships. This could be considered a limitation in the existing body of work, suggesting a need for targeted research in this area. The existence of certain strategies that have proven to enhance supplier partnerships offers a promising avenue for future research. The implications of these findings are twofold. First, organizations in the petroleum and natural gas industry may need to revaluate their F to include a greater focus on buyer-supplier relationship management. Second, academic researchers may consider developing targeted studies that delve into the impacts of these relationships on procurement efficiency and organizational performance. The limitations of this study include the availability of industry-specific reports and the potential for subjectivity in interpreting qualitative data. Future research should aim to mitigate these limitations by employing a more diverse range of data sources and analytical techniques.